1977
DOI: 10.1901/jaba.1977.10-325
|View full text |Cite
|
Sign up to set email alerts
|

TAKING A CLOSER LOOK: TIME SAMPLING AND MEASUREMENT ERROR1

Abstract: A person manufactured his in-seat behavior for 15, 30-min sessions so that there were three blocks of five sessions where the behavior occurred 20%, 50%, and 80% of the time. Whole interval, partial interval, and momentary time-sample measures of the behavior were taken and compared to the continuous measure of the behavior i.e., per cent of time the behavior occurred. For interval time sampling, the difference between the continuous and sample measures i.e., measurement error, was: (1) extensive, (2) unidirec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
97
0

Year Published

1979
1979
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(102 citation statements)
references
References 7 publications
5
97
0
Order By: Relevance
“…The limitations of the three algorithms suggest that other methods, not in common use, should be investigated as well. Further research with real behavioral streams, theoretical analysis (e.g., Hopkins & Hermann, 1977), scripted behavioral interactions (e.g., Van Acker et al, 1991), and studies with manufactured behaviors (e.g., Powell, Martindale, Kulp, Martindale, & Bauman, 1977) are likely to further influence behavior analysts' choice of appropriate agreement and accuracy algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…The limitations of the three algorithms suggest that other methods, not in common use, should be investigated as well. Further research with real behavioral streams, theoretical analysis (e.g., Hopkins & Hermann, 1977), scripted behavioral interactions (e.g., Van Acker et al, 1991), and studies with manufactured behaviors (e.g., Powell, Martindale, Kulp, Martindale, & Bauman, 1977) are likely to further influence behavior analysts' choice of appropriate agreement and accuracy algorithms.…”
Section: Discussionmentioning
confidence: 99%
“…Simply put, the briefer the interval duration, the less systematic error will be introduced into a measurement system, regardless of whether PIR, WIR, or MTS are implemented (Devine, Rapp, Testa, Henrickson & Schnerch, 2011;Hanley, Cammilleri, Tiger, & Ingvarsson, 2007;Powell et al, 1975;Powell et al, 1977;Rapp et al, 2008). However, the decrease in interval duration requires additional effort from data collectors and therefore increases the amount of human error that is introduced during measurement.…”
Section: For What Duration Should Each Interval Last?mentioning
confidence: 99%
“…MTS is not associated with a characteristic direction of error. Because of this fact, MTS will most commonly provide a more accurate estimate of behavioral duration than either PIR or WIR, although the accuracy will be impacted by variables such as behavior duration or level (Ciotti Gardenier, MacDonald, & Green, 2004;Powell, Martindale, & Kulp, 1975;Powell, Martindale, Kulp, Martindale, & Bauman, 1977).…”
Section: What Measurement Error Is Introduced By Discontinuous Measurmentioning
confidence: 99%
“…Researchers have evaluated the extent to which the size of the discontinuous sampling interval influences the degree of error (Mudford, Beale, & Singh, 1990;Powell, Martindale, Kulp, Martindale, & Bauman, 1977;Sanson-Fisher, Poole, & Dunn, 1980). These studies have shown that the accuracy of a discontinuous measure is negatively correlated with the length of the interval between measures, and that this relation is also affected by the overall frequency and stability of the target behaviors as well as bout durations (Powell et al, 1977;Saudargas & Zanolli, 1990). Therefore, analysis of the extent of error introduced by intervals of varying lengths is necessary when developing discontinuous methods to measure activities such as the location and engagement of children in a classroom.…”
mentioning
confidence: 99%